2012
DOI: 10.2105/ajph.2011.300522
|View full text |Cite
|
Sign up to set email alerts
|

High Food Insecurity and Its Correlates Among Families Living on a Rural American Indian Reservation

Abstract: Objectives We examined associations of food insecurity with family sociodemographic characteristics, parents’ and children’s weight, children’s dietary patterns, and the home food environment among American Indian families. Methods Participants were a sample of kindergarten-age children and their parents or caregivers (dyad n = 432) living on the Pine Ridge Reservation in South Dakota who enrolled in the Bright Start study. Parents or caregivers completed a questionnaire on their child’s dietary intake, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(154 citation statements)
references
References 37 publications
7
146
1
Order By: Relevance
“…Researchers have linked food insecurity to obesity in households with children (27), diabetes in adults (28), and poor glucose control for adults who have diabetes (29,30). Food insecurity is found on many reservations where food deserts (i.e., rural, low-income residents must travel more than 10 miles to access supermarkets or grocery stores) are prevalent (31)(32)(33). On a reservation in the Great Plains, 40% of families with children were food insecure.…”
Section: Diabetes and Social Determinants Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have linked food insecurity to obesity in households with children (27), diabetes in adults (28), and poor glucose control for adults who have diabetes (29,30). Food insecurity is found on many reservations where food deserts (i.e., rural, low-income residents must travel more than 10 miles to access supermarkets or grocery stores) are prevalent (31)(32)(33). On a reservation in the Great Plains, 40% of families with children were food insecure.…”
Section: Diabetes and Social Determinants Of Healthmentioning
confidence: 99%
“…On a reservation in the Great Plains, 40% of families with children were food insecure. Much of the food available in homes was purchased at convenience stores on or near the reservation (33).…”
Section: Diabetes and Social Determinants Of Healthmentioning
confidence: 99%
“…15 Food insecure youth have less healthful dietary intake and are at greater risk for nutrient deficiencies than food secure youth. 1625 Food insecurity has also been associated with a higher prevalence of obesity among children and adolescents in some, 2528 but not all, 17,2931 studies. Parenting practices are increasingly being recognized as mediators of the relationship between food insecurity and child-level nutritional and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is consistent with the only other published study that examined the relationship between food insecurity and obesity among AIs/ANs. 4 This study found that 40% of families living on the Pine Ridge Indian reservation reported experiencing food insecurity, but food insecurity was not linked to obesity among either adults or children. 4 Our study is the first to show that a high percentage of low-income urban AIs/ANs are experiencing similar prevalence of food insecurity as AIs/ANs living in rural AI reservation communities.…”
Section: Discussionmentioning
confidence: 67%
“…37 A recent study reported that almost 40% of the families living on an Indian reservation in South Dakota were food insecure. 4 Likewise, in a reservation-based sample of 187 AI households in Montana, 43% of those surveyed were food insecure. 5 Our own previous work with reservation communities in Northern California and Washington uncovered numerous structural and environmental barriers to healthy eating, including geographic isolation, the high cost of fresh vegetables and fruits, and limited access to grocery stores and supermarkets.…”
Section: Introductionmentioning
confidence: 99%